The association between overweight and shock in children with dengue hemorrhagic fever at Wangaya General Hospital, Bali, Indonesia - Jade Irene Linardi; I Wayan Bikin Suryawan; Anak Agung Made Widiasa (DiscoverSys Inc., 2021)
Background: Dengue Hemorrhagic Fever (DHF) which severity varies, has devastating complications and outcomes, especially when shock events appeared and are prolonged. There is no predictor of whether DHF patients would develop into shock (called Dengue Shock Syndrome or DSS). Previous studies claimed overweight as a predictor of DSS, although it remains controversial.Objective: To find the association between overweight and shock events in children with DHF.Methods: This was an observational analytic study with a case-control design. Data were taken from medical records with children hospitalized at Wangaya General Hospital from May 2019 through April 2020. Inclusion criteria were children < 18 years who have been diagnosed with DHF grade I through IV. Data were analyzed using the chi-square test in SPSS 24.0 for windows.Results: Of 126 subjects who fulfilled the inclusion criteria, there were 42 DSS patients as the case group and 84 non-DSS patients as the control group. From the data analysis, there was a significant association between overweight and shock events in children with DHF (p=0.001; OR 3.76; 95% CI 1.72 to 8.20). Furthermore, pleural effusion (p=0.001), highest hematocrit of ? 46% (p=0.001), and lowest platelet count of ? 50,000/µL (p=0.006) also had significant association with shock events.Conclusion: Overweight is associated with shock events in children with DHF. Pleural effusion, hematocrit level of ? 46%, and platelet count of ? 50,000/µL were also counted as risk factors to develop shock.